Ionic-charge dependence of the intermolecular Coulombic decay time scale for aqueous ions probed by the core-hole clock - Pokapanich, Wandared; Kryzhevoi, Nikolai V.; Ottosson, Niklas; Svensson, Svante; Cederbaum, Lorenz S.; Öhrwall, Gunnar; Björneholm, Olle (Journal of the American Chemical Society, 2011)
Auger electron spectroscopy combined with theoretical calculations has been applied to investigate the decay of the Ca 2p core hole of aqueous Ca2+. Beyond the localized two-hole final states on the calcium ion, originating from a normal Auger process, we have further identified the final states delocalized between the calcium ion and its water surroundings and produced by core level intermolecular Coulombic decay (ICD) processes. By applying the core-hole clock method, the time scale of the core level ICD was determined to be 33 ± 1 fs for the 2p core hole of the aqueous Ca2+. The comparison of this time constant to those associated with the aqueous K+, Na+, Mg2+, and Al3+ ions reveals differences of 1 and up to 2 orders of magnitude. Such large variations in the characteristic time scales of the core level ICD processes is qualitatively explained by different internal decay mechanisms in different ions as well as by different ion-solvent distances and interactions.
Gesehen am 03.01.2023